2016
DOI: 10.1126/sciadv.1601026
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and label-free virus enrichment for ultrasensitive virus detection using carbon nanotube arrays

Abstract: Aligned carbon nanotube–integrated device can effectively trap and enrich viruses from field samples without using antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 81 publications
0
95
0
Order By: Relevance
“…We studied whether the sandwich ELISA implemented inside the ZnO‐NIM can improve the sensitivity over the conventional immunoassay for H5N2 AIV detection. The H5N2 AIVs were cultured in embryonated chicken eggs and the concentration of the AIVs was calculated to 3.6 × 10 6 EID mL −1 as our previous report . Serial dilutions of H5N2 AIV samples were prepared for final virus titers of 3.6 × 10 2 , 3.6 × 10 3 , 3.6 × 10 4 , 1.8 × 10 5 , 3.6 × 10 5 , and 3.6 × 10 6 EID 50 mL −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied whether the sandwich ELISA implemented inside the ZnO‐NIM can improve the sensitivity over the conventional immunoassay for H5N2 AIV detection. The H5N2 AIVs were cultured in embryonated chicken eggs and the concentration of the AIVs was calculated to 3.6 × 10 6 EID mL −1 as our previous report . Serial dilutions of H5N2 AIV samples were prepared for final virus titers of 3.6 × 10 2 , 3.6 × 10 3 , 3.6 × 10 4 , 1.8 × 10 5 , 3.6 × 10 5 , and 3.6 × 10 6 EID 50 mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…They have many benefits such as system integration, portability, low sample consumption and waste generation, reagents and time saving, fast mass transfer, and convenience and suitability for portable applications . Microfluidic devices can be employed in the detection of pathogens for practical samples and medical diagnosis . Meanwhile, multiplexed detection is feasible in microfluidic chips with spatial encoding technique .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical methods are label free and can be operated easily and offer excellent flexibility in subsequent molecular analyses and virus culture without affecting virus's capability in pathogenesis and transmission . Among the available methods, size‐based filtration is frequently used . As most of viruses have unique spectra of size distribution, ranging from 20 nm to 400 nm ( Figure A), size‐based isolation can differentiate viruses from impurities, such as proteins and protein complexes of 10 nm and below in size, bacteria and mammalian cells of 1 µm and above in size.…”
Section: Introductionmentioning
confidence: 99%
“…The unique characteristics of nanomaterials, such as large surface‐to‐volume ratio, lightweight, high tensile strength, biocompatibility, and tunable pore size at nanoscale, are particularly appealing for virus isolation and analysis . In our recent study, we successfully demonstrated that the vertically aligned carbon nanotube (CNT) forests with tunable intertubular distance could be integrated into a microfluidic virus isolation device in a dead‐end filtration configuration for virus capture . Isolated viruses are available for subsequent molecular analyses, virus culture, or other virus characterization and studies.…”
Section: Introductionmentioning
confidence: 99%